Progress in research on fresh-keeping, storage and processing technology of Cistanche deserticola - ZHU Zhipeng; BAI Yujia (Shipin yu jixie, 2024)
Cistanche deserticola is one of the precious traditional Chinese medicines that can be eaten fresh. Its highly active life and zoning restrictions cause it to brown, soften, and even mildew when being transported and stored. The processing technology and preservation and storage techniques were analyzed by thoroughly reading literatures in this field. Moreover, the advantages and disadvantages of different processing methods were analyzed, and the development direction of C. deserticola processing technology was prospected.